2020
DOI: 10.1097/qmh.0000000000000288
|View full text |Cite
|
Sign up to set email alerts
|

Effective Organizational Justice and Organizational Citizenship Behavior Using Fuzzy Logic to Obtain the Optimal Relationship

Abstract: Background: Organizational justice (OJ) is important for organizational success; it reflects employee perceptions of fair treatment. OJ promotes employee retention and work engagement toward high performance. Organizational citizenship behavior (OCB) is a discretionary behavior, describing how employees contribute to a smoother organizational performance. OCB enhances employee satisfaction, quality of care, patients' satisfaction with hospital performance, and the use of best hospital practices. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…This study also found that OCB plays a significant role as a mediator of the effect of organizational justice on teachers' task performance. It is in line with previous studies that organizational justice influences OCB (e.g., Donglong et al, 2020;Ajlouni et al, 2021;Widodo&Sulistiasih, 2021), OCB affects task performance (Yang &Chae, 2021;Casu et al, 2021), and organizational justice related to teachers' performance (e.g., Aditya, 2019;Purnama et al, 2020). The indirect effect of organizational justice on task performance mediated by OCB is greater than the direct effect of organizational justice on task performance.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This study also found that OCB plays a significant role as a mediator of the effect of organizational justice on teachers' task performance. It is in line with previous studies that organizational justice influences OCB (e.g., Donglong et al, 2020;Ajlouni et al, 2021;Widodo&Sulistiasih, 2021), OCB affects task performance (Yang &Chae, 2021;Casu et al, 2021), and organizational justice related to teachers' performance (e.g., Aditya, 2019;Purnama et al, 2020). The indirect effect of organizational justice on task performance mediated by OCB is greater than the direct effect of organizational justice on task performance.…”
Section: Discussionsupporting
confidence: 90%
“…The prior studies above indicated that OCB mediates the effect of organizational justice on teachers' task performance. The researchers' investigation indicates that organizational justice influences OCB (e.g., Donglong et al, 2020;Ajlouni et al, 2021;Widodo&Sulistiasih, 2021), meanwhile other studies by Yang and Chae (2021) and Casu et al (2021 show that OCB affects task performance. In practice, when organizational justice manifested in distributive, procedural, and interactional justice (Aamodt, 2016) can realized at school, it potentially enhancing teacher's OCB, such as altruism, conscientiousness, sportsmanship, courtesy, and civic virtue (Organ et al, 2006).…”
Section: Ocbs' Mediating Effectmentioning
confidence: 94%
See 1 more Smart Citation
“…OJ is the most studied field in terms of the OCB context ( Colquitt et al., 2001 ). In addition, several experiments have been performed based on the interaction between the perception of OJ and OCB ( Ajlouni et al., 2021 ; Jnaneswar and Ranjit, 2021 ; Lim and Loosemore, 2017 ). Organ (1988) has revealed that perceived OJ is one of the crucial predictors of OCB.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%